The Influence of Marketing Communication Mix on Decisions to Purchase Room Services - Tigor Halomoan Tambunan; Nidia Wulansari (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
Purchasing decisions refer to the process by which consumers make decisions to buy certain products or services after evaluating the various options available. This activity is one of the utilization of promotional activities carried out by a company. Where in the promotion there are forms of promotion that are incorporated in a marketing communication mix. Marketing communication mix is a form of marketing that is done to attract relationships with consumers while still paying attention to communication values that are useful for building good relationships with consumers. The main objective of this research is to find the correlation between marketing communication mix and the decision to purchase room services. This research uses quantitative methodology with a causal associative approach. Data collection was carried out by distributing questionnaires to respondents in the form of google forms. A total of 165 respondents were surveyed using a Likert scale, and the majority of visitors were in the age range of 26 to 35 years. The data was analyzed using Partial Least Square Structural Equation Modeling. The results showed that F was calculated with sig. 0.000 <0.05, then the marketing communication mix variable has a significant influence on purchasing decisions. Furthermore, R Square is 0.608. This means that the marketing communication mix influences purchasing decisions by 60.8%. This study found that marketing communication mix is an important factor in improving purchasing decisions.